Pressure-induced chemical decomposition of copper orthovanadate (α-Cu3V2O8). Issue 38 (6th September 2021) - Díaz-Anichtchenko, Daniel; Turnbull, Robin; Bandiello, Enrico; Anzellini, Simone; Achary, Srungarpu Nagabhusan; Errandonea, Daniel
Abstract : Out of the large family of orthovanadates, α-Cu3 V2 O8 is found to be most compressible ( B 0 = 52 GPa) and it is the only one to undergo pressure-induced chemical decomposition at very low pressures (~1.35 GPa). Abstract : The high pressure stability of α-Cu3 V2 O8 has been investigated via complementary high pressure synchrotron X-ray diffraction experiments and theoretical density functional theory calculations. The results of both experiment and theory are in close agreement. The main result of this work is that α-Cu3 V2 O8 undergoes a pressure-induced chemical decomposition into CuO and V2 O5 at a modest pressure of ∼1.35 GPa according to the experimental observations, and at ∼2.45 GPa according to the calculations. The decomposition is investigated with enthalpy calculations and one of the main driving factors is the stability of the octhedral oxygen-coordination of the metal atoms in the decompositon products. Additionally, we determine the bulk modulus of α-Cu3 V2 O8 to be the lowest of all known vanadates, at 52(2) GPa, due to its crystal structure, and determine the corresponding isothermal compressibility tensor.